1982
DOI: 10.1111/j.1600-0528.1982.tb01338.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study on oral health of dental students at Paris VII University

Abstract: This survey was conducted on young dental students, with the aim of evaluating the influence of scientific information dispensed during their studies on their own oral state and on their behavior towards it. Therefore, various parameters were considered at the very beginning of their university studies and at the end of their studies. A questionnaire was used to collect information on the socioeconomic origin and oral hygiene habits of the students. In order to assess actual improvement in oral health standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
1
13
1
2
Order By: Relevance
“…In their study, Kumar et al found a similar result. 6 Contrarily, Al-Juboury 13 and Cavaillon et al 29 did not reveal differences between sexes regarding the individual components of DMFT. Overall, females give more importance to dental health than males.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In their study, Kumar et al found a similar result. 6 Contrarily, Al-Juboury 13 and Cavaillon et al 29 did not reveal differences between sexes regarding the individual components of DMFT. Overall, females give more importance to dental health than males.…”
Section: Discussionmentioning
confidence: 88%
“…6,13,29 However, the DMFT individual components revealed better dental health among females. 6,13,29 However, the DMFT individual components revealed better dental health among females.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The frequency of twice daily brushing among dental students in Nigeria is very low (47.5%) compared to their counterparts in Mongolia (81%) [16], France (78%) [21], Iran (57%) [15] and Australia (80%) [22]. It is even less than what has been reported among the general public in Germany, Japan, New Zealand, the USA, and Poland [23], the UK [24] and Finland [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The literature includes some reports on previous studies of dental students' knowledge of and attitude toward preventive dentistry (4,(11)(12)(13)(14)(15)(16), as well as studies on OHB (5,(17)(18)(19)(20)(21)(22). These studies, however, have revealed that cross-cultural differences exist in oral health attitudes and behaviours amongst future oral health professionals in different countries.…”
Section: Discussionmentioning
confidence: 99%